2000
DOI: 10.1258/002367700780384762
|View full text |Cite
|
Sign up to set email alerts
|

Sufentanil and medetomidine anaesthesia in the rat and its reversal with atipamezole and butorphanol

Abstract: SummaryInjectable anaesthetics are widely used to anaesthetize rats, but recovery times are often prolonged. Reversible anaesthetic regimens have the advantage that animals may be recovered quickly, thus reducing the incidence of postoperative complications such as hypothermia, and also providing a means of treating inadvertent anaesthetic overdose. This study assessed and compared the characteristics of anaesthesia induced with combinations of sufentanil and medetomidine administered as a single subcutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 4 publications
(1 reference statement)
1
22
0
Order By: Relevance
“…Although we did not monitor core temperature, the heating pad used throughout the experiment should have helped to prevent hypothermia. In a previous study in rats, the pulse oximeter readings were comparable to arterial blood gas values [40]. Other sources of error could include mechanical artifacts from improper probe placement and electromagnetic interference, but are less likely [39].…”
Section: Discussionmentioning
confidence: 63%
“…Although we did not monitor core temperature, the heating pad used throughout the experiment should have helped to prevent hypothermia. In a previous study in rats, the pulse oximeter readings were comparable to arterial blood gas values [40]. Other sources of error could include mechanical artifacts from improper probe placement and electromagnetic interference, but are less likely [39].…”
Section: Discussionmentioning
confidence: 63%
“…We therefore consider that, in addition to oxygen supplementation, endotracheal intubation of rabbits should be performed as this allows PPV when respiratory depression is severe. Our previous studies (Hedenqvist et al. 2000a, b; 2001) together with subsequent clinical experience have confirmed that endotracheal intubation can be carried out successfully after induction of anaesthesia with ketamine and medetomidine.…”
Section: Discussionmentioning
confidence: 64%
“…Butorphanol appears to be rapidly absorbed following SC injection, as judged by its rapid reversal of µ‐agonists such as fentanyl and sufentanil in rats (Hu et al. 1991; Hedenqvist et al. 2000b; 2001), and experience in our laboratory indicates that it has similarly rapid absorption in rabbits, as judged by its effects in reversing the fentanyl component of ‘Hypnorm’ (Janssen Pharmaceuticals).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calibration curves of each enantiomer were linear over the tested concentration range. Regression equations (the peak area versus the concentration of each enantiomer in ng/mL) showed fairly good linearity with regression coefficients ( r ) of.998 for both levomedetomidine and dexmedetomidine being presented as in Table .…”
Section: Methods Validationmentioning
confidence: 92%